2020
DOI: 10.1371/journal.pone.0234685
|View full text |Cite
|
Sign up to set email alerts
|

Outperforming yet undervalued: Undergraduate women in STEM

Abstract: In spite of efforts to increase gender diversity across many science fields, women continue to encounter beliefs that they lack ability and talent. Undergraduate education is a critical time when peer influence may alter choice of majors and careers for women interested in science. Even in life science courses, in which women outnumber men, gender biases that emerge in peer-to-peer interactions during coursework may detract from women's interest and progress. This is the first study of which we are aware to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 55 publications
0
45
0
7
Order By: Relevance
“…Career progression and retention could also be hindered by persistent stereotypical beliefs about the ability of women in STEM fields. Previous work found that undergraduate women encounter beliefs that their ability and talent is lacking, despite their outperformance of their male colleagues [46]. From the comments of participants, especially those from the mid-and late-career stages, these beliefs seemed to persist, with comments consistently showing women felt a pervasive pressure to prove their worth.…”
Section: Discussionmentioning
confidence: 90%
“…Career progression and retention could also be hindered by persistent stereotypical beliefs about the ability of women in STEM fields. Previous work found that undergraduate women encounter beliefs that their ability and talent is lacking, despite their outperformance of their male colleagues [46]. From the comments of participants, especially those from the mid-and late-career stages, these beliefs seemed to persist, with comments consistently showing women felt a pervasive pressure to prove their worth.…”
Section: Discussionmentioning
confidence: 90%
“…Although women have made significant gains toward equal access to higher education since the 1970s (DiPrete and Buchmann 2013), women continue to be disadvantaged in other aspects. For example, researchers note gender differences in college major choice (e.g., Mullen 2014), in classmates’ perceptions of ability even when women have higher grades in STEM courses (Bloodhart et al 2020), use of time for academic and social purposes (Quadlin 2016), and the gendered sexual script around hooking up (e.g., Hamilton 2014). Another possible inequality can be found in college classrooms, which remain sites of power and privileges.…”
Section: Introductionmentioning
confidence: 99%
“…Os sentimentos de insuficiência e desmotivação acompanham até mesmo as mulheres que têm um bom desempenho durante os cursos relacionados às áreas de Ciência, Tecnologia, Engenharia e Matemática (STEM) e que se identificam com estes [Amaral et al 2017;Bloodhart et al 2020]. Os estereótipos de gênero são problemas culturais reproduzidos por docentes e alunos, através de comentários machistas e tratamento diferenciado, o que gera um desconforto e sentimento de não pertencimento e isolamento por essas alunas [Silva et al 2020].…”
Section: Estudos Relacionadosunclassified